Impact of mycoinsecticides and abamectin applications on species diversity and abundance of aquatic insects in rice fields of freshwater swamps of South Sumatra, Indonesia - Siti Herlinda; Monica Alesia; Susilawati Susilawati; Chandra Irsan; Hasbi Hasbi; Suparman Suparman; Erise Anggraini; Arsi Arsi (Society for Indonesian Biodiversity, 2020)
Abstract. Herlinda S, Alesia M, Susilawati, Irsan C, Hasbi, Suparman, Anggraini E, Arsi. 2020. Impact of mycoinsecticides and abamectin applications on species diversity and abundance of aquatic insects in rice fields of freshwater swamps of South Sumatra, Indonesia. Biodiversitas 21: 3076-3083. Aquatic insects in rice fields generally are predators of rice insect pests. The application of insecticides may reduce the abundance and species diversity of these predators. This study aimed to determine the impact of mycoinsecticides and abamectin application on species diversity and abundance of aquatic insects in rice fields. Mycoinsecticides were made from Beauveria bassiana s.l., Metarhizium anisopliae s.l. and Cordyceps militaris s.l. with carrier from shrimp shell flour compost extract, vegetable oil, and Tween®. The treatments were the mycoinsecticides and abamectin. The results showed there were eight aquatic insects species obtained in this study, i.e. unidentified Dytiscidae, Micronecta sp., Mesovelia sp., Ranatra sp., Anisops sp., Microvelia sp., unidentified species of Veliidae, and Orthetrum sp. belong to 7 families (Dytiscidae, Corixidae, Mesoveliidae, Nepidae, Notonectidae, Veliidae, Libellulidae), and three orders (Coleoptera, Hemiptera, and Odonata). All of the species were predatory insects. The application of mycoinsecticides did not reduce the abundance and species diversity of the aquatic predatory insects, but the application of abamectin reduced the abundance and species diversity of the predators. The highest insect species diversity was in the plots applied with C. militaris s.l., followed by the B. bassiana s.l. and M. anisopliae s.l. plots and the lowest one was found in the abamectin plot. So, the application of mycoinsecticides from B. bassiana s.l., M. anisopliae s.l. and C. militaris s.l. is safe for the aquatic predatory insects and to control rice insect pests than that of abamectin.